Circulating Plasmablasts from Chronically Human Immunodeficiency Virus-Infected Individuals Predominantly Produce Polyreactive/Autoreactive Antibodies - Liao, Hongyan; Yu, Yangsheng; Li, Song; Yue, Yinshi; Tao, Chuanmin; Su, Kaihong; Zhang, Zhixin (Frontiers in Immunology, 2017)
Understanding the B cell response during chronic HIV infection is essential for eliciting broad and potent neutralizing antibodies. In this study, we analyzed the plasmablast repertoire of chronically HIV-infected individuals in combination with antiretroviral therapy (ART). Among the obtained 72 recombinant monoclonal antibodies (mAbs), 27.8% weakly bound to HIV gp140 and were non-neutralizing. Remarkably, 56.9% were polyreactive, and 55.6% were autoreactive. The prominent feature of being polyreactive/autoreactive is not limited to anti-gp140 Abs. Furthermore, these polyreactive/autoreactive antibodies displayed striking cross-reactivity with DWEYS in the N-methyl-D-aspartate receptor (NMDAR), and this binding induced SH-SY5Y cell apoptosis. We also found higher frequencies of VH4-34 utilization and VH replacement in the plasmablast repertoire of chronically HIV-infected individuals, which may contribute to the generation of poly/autoreactive Abs. Taken together, these data demonstrate that circulating plasmablasts in chronically HIV-infected individuals experienced with ART predominantly produce poly/autoreactive Abs with minimal anti-HIV neutralizing capacity and potential cross-reactivity with autoantigens. This may represent another dysfunction of B cells during chronic HIV infection.